Optical Controlled Terahertz Modulator Based on Tungsten Disulfide Nanosheet. Issue 1 (December 2017) - Fan, Zhiyuan; Geng, Zhaoxin; Lv, Xiaoqin; Su, Yue; Yang, Yuping; Liu, Jian; Chen, Hongda
Abstract The terahertz (THz) modulator, which will be applied in next-generation wireless communication, is a key device in a THz communication system. Current THz modulators based on traditional semiconductors and metamaterials have limited modulation depth or modulation range. Therefore, a THz modulator based on annealed tungsten disulfide (WS2, p-type) and high-resistivity silicon (n-type) is demonstrated. Pumped by a laser, the modulator presents a laser power-dependent modulation effect. Ranging from 0.25 to 2 THz, the modulation depth reaches 99% when the pumping laser is 2.59 W/cm2 . The modulator works because the p-n heterojunction can separate and limit carriers to change the conductivity of the device, which results in a modulation of the THz wave. The wide band gap of WS2 can promote the separation and limitation of carriers to obtain a larger modulation depth, which provides a new direction for choosing new materials and new structures to fabricate a better THz modulator.